2006
DOI: 10.1677/joe.1.07009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the human WISP-2/CCN5 gene promoter reveal its upregulation by oestrogens

Abstract: Wnt-1-induced signalling pathway protein-2 (WISP-2)/ connective tissue growth factor/cysteine-rich 61/nephroblastoma overexpressed (CCN)5 is a member of the CCN family of growth factors and was identified as an oestrogen-inducible gene in the MCF-7 cell line. However, the role of WISP-2/ CCN5 in breast carcinogenesis remains unclear. In this study, we examined the mechanism by which oestrogens regulate the expression of human (h) Wnt-1 induced signalling pathway protein (WISP-2)/CCN5. Real-time RT-PCR showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…However, their effect in terms of offering new concepts of the molecular network of human breast cancer development, diagnostics, or therapeutic modalities remains limited. Over the last several years, after the identification of CCN5 in noninvasive human breast tumor cells and samples by using RNA differential display analysis (14), CCN5 has been implicated as having an important role in human breast disease and other cancers as well (9,10,14,20,(29)(30)(31)(32)(33). The present immunohistochemical and in situ hybridization analysis studies have shown a differential expression profile of CCN5 in human breast samples.…”
Section: Discussionmentioning
confidence: 57%
“…However, their effect in terms of offering new concepts of the molecular network of human breast cancer development, diagnostics, or therapeutic modalities remains limited. Over the last several years, after the identification of CCN5 in noninvasive human breast tumor cells and samples by using RNA differential display analysis (14), CCN5 has been implicated as having an important role in human breast disease and other cancers as well (9,10,14,20,(29)(30)(31)(32)(33). The present immunohistochemical and in situ hybridization analysis studies have shown a differential expression profile of CCN5 in human breast samples.…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have shown that nucleotide alterations from the core sequence on each side of an ERE palindrome, results in a significant decrease in ER-binding affinity and transcriptional activation (Klinge 2001). This lack of sequence identity with a canonical ERE does not preclude direct ligand-activated ER regulation as demonstrated for the imperfect ERE present in the proximal promoter of the human WISP2 gene (5 0 -GGTCA-CAC-CCACC-3 0 ) (Fritah et al 2006). Therefore, we directly tested the hormone inducibility of the STC2 proximal promoter region; however, E 2 , RA or P4 treatments did not induce the STC2 promoter.…”
Section: Transcriptional Regulation Of Stc2 Expression By Oestrogen Amentioning
confidence: 99%
“…*, P < 0.01 versus controls. B, schematic representation of the minimal hCCN5 promoter that was recently cloned and characterized (49). Estrogen response element is shown as ERE motif here.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%